Premna mwadimei (Lamiaceae), a new species from Cha Simba, a remnant of coastal forests of Kenya, East Africa - Ngumbau, Veronicah Mutele; Musili, Paul Mutuku; Hu, Guang-Wan (Phytotaxa, 2021)
Premna mwadimei (Lamiaceae), a distinct new species from the coastal forests of Kenya, Cha Simba area in Kilifi County, is described here with photographs. It is closely similar to P. chrysoclada and P. tanganyikensis but mainly differs from both by its habit, nature of the older stems, indumentum, leaf shape and floral morphology.